AB0858 Impact of application of asas criteria for axial spondyloarthritis on the diagnostic delay in egyptian patients. (12th June 2018) - Abdelrahman, F.I.; Mortada, M.
Abstract : Background: Diagnostic delay is a major challenge in axial spondyloarthritis(SpA). The 2009 Assessment of SpondyloArthritis international Society classification(ASAS) criteria for axial SpA formally recognised the utility of MRI in diagnosis. 1 There are conflicting reports whether there had been any recent improvement in the period of diagnostic delay after application of ASAS criteria. 2 Objectives: To evaluate the period from symptoms onset to diagnosis in Egyptian patients with axial SpA before and after application of ASAS criteria for axial SpA and to examine possible reasons for delayed diagnosis. Methods: The study included all axial SpA patients attending a university tertiary referral centre for regular follow up in the period between May 2016 to November 2017. The patients were divided into 2 groups; group 1 included patients with a diagnosis of axial SpA before the beginning of 2010 (when ASAS criteria became widely available and in use) and group 2 included patients with a diagnosis of axial SpA after the beginning of 2010. A face-to-face interview was applied for both groups to take medical history, and a questionnaire that contains some clinical aspects of disease was used. Diagnosis delay was described as the gap between first SpA symptom and correct diagnosis of axial SpA. Clinical and functional assessment of axial SpA measured by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI). The direct medical cost during years of delay (including costs of medical consultations, medications, investigations, physiotherapy and surgical treatment) had been estimated. Results: As presented in table 1; more axial SpA cases were in group 2 (diagnosed after the beginning of 2010) with significantly narrower gap of delay, younger age at diagnosis, lesser number of doctor visits, lesser number of unnecessary spinal surgeries, lower total direct estimated costs and better BASDI, BASFI and BASMI. Conclusions: Application of ASAS criteria for axial SpA has resulted in a significant decrease in the diagnostic gap which is reflected in a significant decrease in age at diagnosis and in the costs of unnecessary medications. On the other side, the gap is still large and more sensitive criteria are still needed. References: [1] Rudwaleit M. et al: The development of Assessment of Spondyloarthritis international Society classification criteria for axial spondyloarthritis; Ann Rheum Dis, 68 (2009), pp.777–783. [2] Sykes M. et al: Diagnostic delay in patients with rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis; Ann Rheum Dis.2015;74:e44. Disclosure of Interest: None declared